Irrigation Scheduling to Promote Corn Productivity in Central Alabama - Da Cunha Leme Filho, Jose F. (2020)
Agriculture is the largest consumer of water in the United States. Results from previous studies have shown thatit is possible to substantially reduce irrigation amounts and maintain corn yield. The objectives of this study wereto evaluate the advantages and disadvantages of two irrigation scheduling methods for corn production inAlabama. Two irrigation scheduling methods evaluated were: a) Checkbook, which is one of the conventionalmethods used by farmers that is based on the soil water balance estimated using water lost by evapotranspirationand its replacement through rainfall or irrigation, and b) Sensor-based, which was based on soil matric potentialvalues recorded by soil moisture tension sensors installed in the field. The experimental field was divided intotwo irrigation management zones (zone A and zone B) based on soil properties of each field. During the 2014season in zone A, significant grain yield differences were observed between the two irrigation methods. TheCheckbook plots exhibited greater yield than Sensor-based plots: 10181 kg ha-1 and 9696 kg ha-1, respectively.The greater yield on the Checkbook plots could be associated with higher irrigation rate applied, 148 mm more,compared with the Sensor-based plots. In zone B, there were no significant yield differences between bothirrigation methods; however, Sensor-based plots out yielded Checkbook plots, with 9673 kg ha-1 and 9584 kgha-1, respectively. Even though the irrigation amount applied in Checkbook located in zone B was higher, 102mm more, there were no significant yield differences. Therefore, it suggests that the Sensor-based method waspromissory irrigation scheduling strategy under the conditions of zone B. In 2015, there were no significant grainyield differences between zone A and zone B when the data from the Checkbook plots were analyzed. However,the Sensor-based treatment produced a statistically significant difference of grain yield of 13597 kg ha-1 in zoneA and 11659 kg ha-1 in zone B, also both zones received the same amount of irrigation. Overall results of bothgrowing seasons indicated that the use of the Sensor-based irrigation scheduling treatment resulted in similarvalues of total profit per hectare when compared to Checkbook method. The Sensor-based method seems apromising strategy that could result in water and financial savings, but more research is required.